2017
DOI: 10.1016/j.ijthermalsci.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Monte-Carlo parallel simulation of phonon transport for 3D silicon nano-devices

Abstract: Due to the importance of the transistors in nano-electronics technology, the accurate study of these nano-devices is an essential field of research. Taking into account the non-Fourier nature of heat transfer with considering the actual three-dimensional structure of the MOSFETs, are the challenges in transistor analysis which have not been studied precisely yet. Using the Monte-Carlo method for solving the Boltzmann equation, two actual threedimensional silicon transistors are accurately simulated. First, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 46 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…As a phonon scatters, its frequency, branch and direction will be re-sampled from the cumulative density function [31]. Here, the time step, ∆t is chosen to be smaller than the minimum scattering rate of the phonons which are sampled during the simulation.…”
Section: D Materials Graphene Blue Phosphorene Germanenementioning
confidence: 99%
See 2 more Smart Citations
“…As a phonon scatters, its frequency, branch and direction will be re-sampled from the cumulative density function [31]. Here, the time step, ∆t is chosen to be smaller than the minimum scattering rate of the phonons which are sampled during the simulation.…”
Section: D Materials Graphene Blue Phosphorene Germanenementioning
confidence: 99%
“…The value of the self-heating source is assumed to be Q=2.5×10 12 W/m 3 . All boundaries of the investigated new low-dimensional materials are assumed to be adiabatic except the bottom boundaries which can exchange the energy with the environment [31,32]. Consequently, the temperature at these boundaries are set to the ambient temperature.…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BE has been widely used in a range of fields spanning from gasses, plasma, and semiconductor's physics (we focus here specifically on the time-dependent equation) [43][44][45][46][47][48][49][50]. The transport part has a similar shape in all those fields, with the only notable exception that in solid state applications, the particle's dispersion is not anymore a quadratic function of the momentum, but is in general much more complicated and often an analytic form is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Harada et al [24] applied the semi-classical MC method to silicon and monolayer graphene devices, and compared the differences in electron transport properties that arise due to the linear band dispersion of graphene. Shomali et al [25] performed energy carrier transport simulations using the MC method to investigate the effects of boundary conditions on the temperature distribution profiles and localized hotspots in silicon nanodevices. Fang et al [26] demonstrated the contribution of both acoustic and optical phonon emission to the energy loss in silicon and germanium devices through full-band MC simulations.…”
Section: Introductionmentioning
confidence: 99%